THE ROLE OF AUDIT OPINION MODERATION IN AUDITOR SWITCHING - Aan Kanivia; Abdisamad Abdirahman Omar; Arief Nurhandika; Dessy Kumala Dewi; Safitri Akbari (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2025)
Relevant research indicates that new management is likely to replace auditors to align financial reporting, while other research suggests that auditors can be retained if their performance is deemed adequate. This study investigates whether audit opinions can moderate the relationship between management turnover and auditor turnover. This study uses a quantitative approach by utilizing secondary data. Data is collected through a purposive sampling process. The study analyzed information from 22 energy companies operating in the oil, gas, and coal sectors from 2019–2023. Regression analysis was carried out using STATA 17 by applying logistic regression analysis and MRA. The results showed that management change had a positive effect on auditor turnover, with the influence partially moderated by audit opinion.